2015
DOI: 10.1177/0194599815575713
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Increases the Risk of Sudden Sensorineural Hearing Loss in Taiwan

Abstract: These results suggest that metabolic syndrome is an independent risk factor for sudden sensorineural hearing loss in Taiwan. Vertigo and total hearing loss were indicators of a poor outcome in sudden sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 27 publications
6
61
0
15
Order By: Relevance
“…These co-morbidities might interfere with the microvascular supply of the inner ear and lead to hearing loss. Although their effect on prognosis of the disease is not well established, it may be speculated that negative prognostic effect may occur (17,18). Thus, despite steroids seeming to have no additional benefit in this paper, studies on more homogenous patient populations might contribute to the knowledge.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These co-morbidities might interfere with the microvascular supply of the inner ear and lead to hearing loss. Although their effect on prognosis of the disease is not well established, it may be speculated that negative prognostic effect may occur (17,18). Thus, despite steroids seeming to have no additional benefit in this paper, studies on more homogenous patient populations might contribute to the knowledge.…”
Section: Discussionmentioning
confidence: 81%
“…The negative prognostic effect of profound or total hearing loss is almost agreed worldwide. However, in the literature, there are certain studies which report poor prognosis with flat type or low frequency losses which is an inconsistent finding with the majority of the rest (18,25). This might be attributable, to a certain point, to various classification patterns or diverse treatment modalities utilized by different authors.…”
Section: Discussionmentioning
confidence: 98%
“…Age ( p  = 0.003), vertigo ( p  = 0.006), and initial hearing loss ( p  < 0.001) were positively correlated with final outcome, while BMI ( p  = 0.23), tinnitus ( p  = 0.30) and sex ( p  = 0.878) were not. Other data (severity of hearing loss, time to treatment, BMI, vertigo) were identified as negative prognostic factors of SISHL in other trials [2225]. When we performed the same analysis adjusted for therapeutic benefit (difference between initial and final hearing loss), only patients with higher initial hearing loss showed a significant positive correlation with hearing improvement ( p  < 0.001).…”
Section: Discussionmentioning
confidence: 77%
“…Vascular compromise and associated cochlear ischemia are thought to be contributory to SISHL in some cases, or could be a final common pathway to hearing loss. And indeed atherosclerotic and rheological risk factors (hypercholesterolemia [2022], hyperfibrinogenemia [23], age [24], BMI [22], metabolic syndrome [25] or hyperhomocysteinemia [26]) have recently been proven to be important in the etiology and prognosis of SISHL, although not all studies support such evidence [27, 28]. When analyzing our data, we cannot confirm an elevated baseline level of LDL-cholesterol, fibrinogen or viscosity in SISHL patients.…”
Section: Discussionmentioning
confidence: 99%
“…GPX3 polymorphisms have been associated with cardiovascular risk in a Mexican population [20]. A previous study showed that MetS is an independent risk factor for SSNHL in Taiwan after adjusting for potential confounding factors (adjusted OR Z 3.54, p < 0.01) [21]. The T allele frequency for rs3828599 of GPX3 is significantly lower in hypertensive patients than in controls (35.6% vs. 40.8%, p Z 0.009) in the Han Chinese population in China [22].…”
Section: Discussionmentioning
confidence: 96%